Functional silicon nanostructures derived from drying-mediated self-assembly of gold nanoparticles - Deshmukh, Ashvini B.; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Journal of Nanoparticle Research, 2014)
Self-assembly of nanoparticles is an efficient technique where nanobuilding blocks spontaneously organize into ordered structures by thermodynamic and other constraints. We demonstrate that multifunctional Silicon (Si) nanostructures with unique morphologies like sheets, plates and flakes can be etched chemically by taking an advantage of natural self-assembly of gold nanoparticles (AuNPs) characterized with drying kinetics under external stimuli. We further demonstrated antireflection properties of the as-synthesized Si nanostructures.
Keywords: Antireflective material; gold nanoparticles; Metal-assisted chemical etching; Self-assembly; Si Nanostructures

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Facile synthesis and self-cleaning application of bimetallic (CuSn, CuNi) dendrites - Biswas, Anupam; Kulkarni, Mayuresh A.; Bakthavatsalam, Rangarajan; Mondal, Sourik K.; Dwivedi, Pravin K.; Shelke, Manjusha V.; Devi, Radhamonyamma N.; Banpurkar, Arun G.; Kundu, Janardan (Chemistryselect, 2017)
Bimetallic dendrites (Au, Ag, Pt, Pd) have received intense research interest due to their applications in catalysis and sensing. However, reports on rational synthesis of non-noble bimetallic dendrites that finds self-cleaning applications are scanty. Here, we demonstrate one step co-reduction based galvanic replacement reaction (GRR) for synthesis of alloyed bimetallic dendrites (CuSn, CuNi) with controlled surface roughness and chemical composition. Probing their growth process reveals that i) for CuSn dendrites, co-reduction of Cu2+ and Sn2+ is observed throughout GRR; ii) for CuNi dendrites, Cu nanoparticle, that deposits initially, augments the reduction of Ni2+ which leads to CuNi alloy phase formation during later stages of GRR. These dendrites, naturally having dual degree of surface roughness (micro/nano), have been exploited here for fabricating superhydrophobic surfaces (SHS) with excellent self-cleaning abilities. They show enabling properties such as high contact angle, minimal contact angle hysteresis, and excellent Cassie state stability with no impalement. They maintain superhydrophobicity when exposed to different environmental conditions (low temperature, high temperature, exposure to corroding solutions and UV radiation). The present facile methodology for fabrication of bimetallic dendrites is beneficial for low-cost production of functional nano/micro-materials.

Facile synthesis of 3D anode assembly with Si nanoparticles sealed in highly pure few layer graphene deposited on porous current collector for long life Li‐Ion battery - Shelke, Manjusha V.; Gullapalli, Hemtej; Kalaga, Kaushik; Rodrigues, Marco; Devarapalli, Rami Reddy; Vajtai, Robert; Ajayan, Pulickel M. (Advanced Materials Interfaces, 2017)
With its exceptional theoretical charge capacity, silicon holds great promise as an anode material for realization of high energy density Li-ion batteries. However, extensive volume expansion and poor cycle stability of silicon compromise its actual use. In an effort to tame volume expansion and structural disintegration during cycling, an innovative 3D electrode assembly is fabricated involving continuous layer of graphene coated on porous current collector and Si nanoparticles sealed in as an active material. Graphene deposition and pore formation in metal current collector is achieved in a unique single step synthesis. All the active components like current collector, reacting material, and conducting material are manipulated in a way to produce synergistic architecture in a chemical vapor deposition process. Highly pure graphene deposited in this process enables efficient electron transfer from allover of the surface of silicon nanoparticles and prevents continuous solid electrolyte interphase layer formation. This binder free anode assembly shows extremely stable lithium storage performance for over 1000 cycles with 88% of initial capacity retention and 100% Coulombic efficiency.

Facile synthesis of unique cellulose triacetate based flexible and high performance gel polymer electrolyte for lithium ion batteries - Nirmale, Trupti C.; Karbhal, Indrapal; Kalubarme, Ramchandra S.; Shelke, Manjusha V.; Varma, Anjani J.; Kale, Bharat B. (ACS Applied Materials & Interfaces, 2017)
Lithium ion batteries (LIBs) with polymer based electrolytes have attracted enormous attention due to the possibility of fabricating intrinsically safer and flexible devices. However, economical and eco-friendly sustainable technology is an oncoming challenge to fulfill the ever increasing demand. To circumvent this issue, we have developed a gel polymer electrolyte (GPE) based on renewable polymers like cellulose triacetate and poly (polyethylene glycol methacrylate) p(PEGMA) using a photo polymerization technique. Cellulose triacetate offers good mechanical strength with improved ionic conductivity, owing to its ether and carbonyl functional groups. It is observed that the presence of an open network has a critical impact on lithium ion transport. At room temperature, GPE PC exhibits an optimal ionic conductivity of 1.8 x 10(-3) S cm(-1) and transference number of 0.7. Interestingly, it affords an excellent electrochemical stability window up to 5.0 V vs Li/Li+. GPE PC shows a discharge capacity of 164 mAhg(-1) after the first cycle when evaluated in a Li/GPE/LiFePO4 cell at 0.5 C-rate. Interfacial compatibility of GPE PC with lithium metal improves the overall cycling performance. This system provides a guiding principle toward a future renewable and flexible electrolyte design for flexible LIBs (FLIBs).

Flexible ultracapacitor device fabricated with an organic electrode material- naphthalene diimide nitrile/reduced graphene oxide - Deshmukh, Ashvini B.; Biradar, Madan R.; Pawar, Meenakshi D.; Bhosale, Sidhanath V.; Shelke, Manjusha V. (Journal of Energy Storage, 2022)
In this work, we have demonstrated a high-performance flexible supercapacitor electrode based on reduced graphene oxide (rGO) and naphthalene diimide nitrile (NDI-CN) composite. The rGO/NDI-CN composite was prepared by a simple approach. This composite was well characterized using various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) etc. Besides, the pi -pi stacking of NDI-CN on rGO surface was confirmed using UV-vis and FTIR techniques. As fabricated rGO/NDI-CN composite was examined as an electrode material for the supercapacitor applications. The rGO/NDI-CN electrode has delivered an excellent specific capacitance (C-sp) of 336 F g(-1) at 0.5 A g(-1)current density. The fabricated supercapacitor (SC) displays robustness with 80 % capacitance retention over 10,000 cycles at higher current density of 10 A g(-1). To further explore the real-world application of electrode materials, the corresponding flexible supercapacitor was designed and examined. The flexible device exhibited an energy density of 9.54 mu Wh cm(-2) at a power density of 0.3 mWcm(-2). These results confirmed that the rGO/NDI-CN electrode material has good potential as an energy storage device. Furthermore, the facile construction and fabrication of flexible device displayed operation of LED when fully charged. The assembled flexible supercapacitor device could be bent and twisted, signifying the potential to be used in practical applications in various high-performance electrochemical devices.
Keywords: flexible supercapacitor; Naphthalene diimide; Organic molecule electrodes; pi -pi interaction; rGO

Few-layer graphene lithiophilic and sodiophilic diffusion layer on porous stainless steel as lithium and sodium metal anodes - Patrike, Apurva; Wasnik, Kundan; Shelke, Manjusha V. (Chemistry-An Asian Journal, 2023)
In order to subdue the obvious problem of uneven electric field distribution on regularly used copper/aluminum current collectors for alkali metal batteries, graphene on porous stainless steel (pSS_Gr) was fabricated using the ion etching technique that is employed as an effective host for lithium and sodium metal anodes. The binder-free pSS_Gr demonstrated stable Li plating and stripping at areal current and capacity of 6 mA cm(-2) and 2.54 mAh cm(-2), respectively, for over 1000 cycles with 98% coulombic efficiency (C.E.). Also, in the case of Na metal anode, the host has shown stable performance at 4 mA cm(-2) and 1 mAh cm(-2) over 1000 cycles with similar to 100% C.E.. Further, a full cell composed of Li-plated pSS_Gr as an anode and LiFePO4 as a cathode is electrochemically tested at 50 mA g(-1) current density with stable 100 cycles.
Keywords: Few layer graphene; Free-standing; Li and Na metal functional host; Na depth profiles; post-cycling XPS